Identification of Polerovirus Infecting Chili Pepper in Java - Andri Saputra; Giyanto; Sari Nurulita; Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2025)
Infection of polerovirus in chili peppers has been reported from various parts of the world, including Indonesia. Pepper vein yellow virus (PeVYV), a member of genus Polerovirus were reported infecting chili plants in Bali, Java, and Aceh during 2012 to 2020. Recently, symptoms of the polerovirus infection, such as yellowing leaves with vein thickening, were found in chili pepper crops in the Central Java Region, specifically in Brebes, Magelang, and Kulon Progo. Molecular detection by RT-PCR method using universal polerovirus primers O3R/PL4F, followed by sequence analysis, confirmed the presence of PeVYV on samples from Magelang and Kulon Progo. Furthermore, the isolates of PeVYV are identified as PeVYV-2, PeVYV-6, and PeVYV-8. These current incidences indicate the expansion of the Polerovirus distribution in Indonesia.